COX-2 expression in mammary invasive micropapillary carcinoma is associated with prognostic factors and acts as a potential therapeutic target in comparative oncology - Vieira, Thaynan Cunha; Oliveira, Evelyn Ane; Santos, Bárbara Jaime dos; Souza, Fernanda Rezende; Veloso, Emerson Soares; Nunes, Cristiana Buzelin; Del Puerto, Helen Lima; Cassali, Geovanni Dantas (Frontiers in Veterinary Science, 2022)
Human and canine mammary invasive micropapillary carcinoma is a rare malignant epithelial tumor accounting for 0.9 to 2% of all human invasive breast carcinomas and present a high rate of lymphatic invasion and metastasis, with unfavorable prognosis due to the aggressive behavior and low survival rate. Surgery and chemotherapy are the most common treatments for breast cancer, as well as hormonal and target therapies available for human patients. However, satisfactory results are a challenge due to the limited effective therapeutic options available for the aggressive behavior of such tumor. Cyclooxygenase-2 (COX-2) isoform is stimulated by cytokines, growth factors and oncogenes activation and plays a key role in cancer development, disease progression, tumor recurrence and regional lymph node metastasis in human and canine mammary carcinomas. COX-2 can be targeted by non-steroidal anti-inflammatory drugs and its selective inhibition can reduce tumor growth and metastasis. Given the similarity between both species, the present study aims to elucidate the involvement of COX-2 mRNA and protein expression, specifically in canine (cIMPC) and human (hIMPC) invasive mammary micropapillary carcinoma, with clinicopathological data. Twenty-nine cIMPC and 17 hIMPC were analyzed regarding histologic type, grade, age, tumor size, lymph node condition, extracapsular extension, inflammatory infiltrate and immunophenotype. When available, information on adjuvant treatment, recurrence, metastasis and survival times were collected. The present study demonstrated COX-2 protein expression in 65.5% of cIMPC and 92.3% of hIMPC, and an association with more advanced histological grades in bitches and higher Ki67 in women. COX-2 mRNA expression was significantly higher in cIMPC than in hIMPC, but its expression did not correlate with COX-2 protein expression in both species. COX-2 mRNA expression was associated with negative-ER hIMPC as well as higher Ki67. This is the first time COX-2 expression is associated with negative prognostic factors in both cIMPC and hIMPC, besides the high frequency of COX-2 protein expression in such unfavorable histological type, which suggests COX-2 is a potential target in IMPC to contribute with better outcomes in canine and human patients.